2017
DOI: 10.1016/j.foodres.2017.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Extensive profiling of three varieties of Opuntia spp. fruit for innovative food ingredients

Abstract: A B S T R A C TConsumer interest in the use of natural ingredients is creating a growing trend in the food industry, leading to research into the development of natural products such as colorants, antimicrobials and antioxidant compounds. This work involves an extensive morphological (using physico-chemical assays), chemical (antioxidant activity assays) and microbiological (Gram-positive and negative strains) characterization of prickly peras (Opuntia ficusindica (OFI) var. sanguigna, gialla and Opuntia engel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 33 publications
0
11
0
2
Order By: Relevance
“…Out of the seven betacyanins identified, six common Opuntia spp. isomers were found, betanin, isobetanin, gomphrenin I, 17-decarboxy-betanin, betanidin, and isobetanidin (peaks Bc1, Bc2, Bc3, Bc5, Bc6, and Bc7, respectively), having been previously identified by other authors [16,22,23,24]. Thus, (Iso)phyllocactin (peak Bc4) has not been previously identified in Opuntia spp., it has been already described in Cactaceae [25,26,27] and in red beets [28,29], as far as we know, this is the first attempt at tentatively identifying this molecule in O. engelmannii .…”
Section: Resultsmentioning
confidence: 59%
“…Out of the seven betacyanins identified, six common Opuntia spp. isomers were found, betanin, isobetanin, gomphrenin I, 17-decarboxy-betanin, betanidin, and isobetanidin (peaks Bc1, Bc2, Bc3, Bc5, Bc6, and Bc7, respectively), having been previously identified by other authors [16,22,23,24]. Thus, (Iso)phyllocactin (peak Bc4) has not been previously identified in Opuntia spp., it has been already described in Cactaceae [25,26,27] and in red beets [28,29], as far as we know, this is the first attempt at tentatively identifying this molecule in O. engelmannii .…”
Section: Resultsmentioning
confidence: 59%
“…Melgar et al . () reported that betalains are almost water soluble pigments, but they are also slightly soluble in ethanol (Damit et al ., ). However, Damit et al .…”
Section: Resultsmentioning
confidence: 99%
“…Nutritional value (protein, fat, carbohydrates and ash content) was determined according to AOAC procedures (AOAC, 2016), following methods described by Melgar et al (2017). For the protein content evaluation, a macro-Kjeldahl method (N × 6.25) was used; the crude fat was determined using a Soxhlet apparatus, extracting the sample with petroleum ether; ash content was estimated by incineration at 600 ± 15°C during 5 h; total carbohydrates were calculated by difference; and the energy content was determined applying the equation: Energy (kcal) = 4 × (g protein + g carbohydrates) + 9 × (g fat).…”
Section: Nutritional Value and Chemical Compositionmentioning
confidence: 99%